2002
DOI: 10.1152/japplphysiol.00277.2002
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids modulate the biophysical properties and vasoactivity of PACAP-(1—38)

Abstract: The purpose of this study was to elucidate the interactions between pituitary adenylate cyclase-activating peptide (PACAP)-(1--38) and phospholipids in vitro and to determine whether these phenomena modulate, in part, the vasorelaxant effects of the peptide in the intact peripheral microcirculation. We found that the critical micellar concentration of PACAP-(1--38) was 0.4-0.9 microM. PACAP-(1--38) significantly increased the surface tension of a dipalmitoylphosphatidylcholine monolayer and underwent conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To this end, we showed that self-association of amphipathic peptide drug candidates, such as vasoactive intestinal peptide (VIP), with long-circulating, biocompatible and biodegradable sterically stabilized phospholipid nanomicelles (SSM) increases peptide stability in vitro and prolongs and amplifies its bioactivity in vivo (Önyüksel et al, 1999;Tseushita et al, 2002;Krishnadas et al, 2003). Importantly, given their distinct physico-chemical characteristics, these nanosized constructs are preferentially targeted to inflamed and injured tissues through local 'leaky' microcirculation (Sethi et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we showed that self-association of amphipathic peptide drug candidates, such as vasoactive intestinal peptide (VIP), with long-circulating, biocompatible and biodegradable sterically stabilized phospholipid nanomicelles (SSM) increases peptide stability in vitro and prolongs and amplifies its bioactivity in vivo (Önyüksel et al, 1999;Tseushita et al, 2002;Krishnadas et al, 2003). Importantly, given their distinct physico-chemical characteristics, these nanosized constructs are preferentially targeted to inflamed and injured tissues through local 'leaky' microcirculation (Sethi et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Neuropeptide receptor up‐regulation in the lung is described in idiopathic pulmonary arterial hypertension (IPAH) [11] and pulmonary inflammation [26] which may contribute to sustained peptide stability by immediate receptor binding of VIP or PACAP. Tsueshita and Krishnadas have shown that phospholipids stabilize and modulate the biophysical properties of PACAP [48,52], which may play an important role in the interaction of PACAP with surfactant which is a mixture of several phospholipids. Furthermore, it has been suggested that inhalative application of VIP (200 µg divided into 4–6 doses) could serve as an effective drug for treatment of IPAH [11].…”
Section: Discussionmentioning
confidence: 99%
“…PACAP38 in conscious rats. It indicates that the thermoregulatory (constrictor) effect of PACAP38 on the cutaneous vascular tone is different from its direct (dilator) effect on skin vessels, which was shown earlier in small rodents (Absood et al 1992; Tsueshita et al 2002). The initial drop of HLI lasted for 40 min, and then, it was followed by a pronounced elevation of HLI due to tail skin vasodilation, which remained significantly (p<0.05) higher than the HLI of saline-treated rats until the end of the experiment in accordance with the vasodilatory effect of PACAP38 reported earlier (Absood et al 1992; T sueshitaetal.2002).…”
Section: Characteristics Of the Thermoregulatory Response To Central (Icv) Pacap38 Administrationmentioning
confidence: 82%